Notes on the geographic distribution and subspecific taxonomy of Sais rosalia (Cramer) (Lepidoptera, Nymphalidae, Ithomiini), including the first records in Paraguay - Ríos Díaz,Sergio D. (2014)
Notes on the geographic distribution and subspecific taxonomy of Sais rosalia (Cramer) (Lepidoptera, Nymphalidae, Ithomiini), including the first records in Paraguay. This paper provides comments on the subspecific taxonomy and geographic distribution of Sais rosalia (Cramer, 1779) (Lepidoptera, Nymphalidae, Ithomiini), as well as an up-to-date distributional map, complemented with unpublished distributional data based on specimens deposited in the Coleção Entomológica Pe. Jesus S. Moure, Curitiba, Brazil and the Museo de Historia Natural, Lima, Peru. The following synonyms are proposed: Sais rosalia camariensis Haensch, 1905 syn. rev. as junior subjective synonym of Papilio rosalia Cramer, 1779 and Sais rosalia brasiliensis Talbot, 1928 syn. rev. as junior subjective synonym of Sais rosalia rosalinde Weymer, 1890. Additionally, the first country records of Sais rosalia in Paraguay, including the southernmost record of the species, are documented.